العمارة الدينية الأثرية بمنطقة الزاب ومتطلبات توظيفها في تنمية السياحة الدينية - بن قربة, صالح; شلـوق, فتيحة (Sciences humaines; Vol. 35 (2014): SCIENCES HUMAINES, 2014)
العمارة الإسلامية متنوعة منها: المدنية كالقصور والمساكن والمصانع، والعسكرية كالأربطة والأسوار والحصون والأبراج والقلاع، والدينية كالمساجد والزوايا والأضرحة...، وفي مقالنا هذا نحاول التعريف بمختلف معالم العمارة الدينية الإسلامية الأثرية بمنطقة الزاب ومتطلبات توظيفها في تنمية السياحة الدينية، على اعتبار أن للسياحة دور فعال في استغلال أمثل للموارد المتاحة الطبيعية منها والبشرية والحضارية والتاريخية وبالتالي المساهمة في تسويد المصفوفة القطاعية بما يوفر مناصب شغل وخلق فرص مدرة للدخل وتحسين ميزان المدفوعات، فضلا عن المساهمة في تحسين أسلوب ونمط الحياة الاجتماعية والثقافية لمختلف أفراد المجتمع.   Islamic architecture is varied, (Civil construction: Palaces, houses and factories, and military: Rabats, fences, forts, towers, castles, and religious: mosques, zaouïas, Shrines…), in this article we try definition of various websites, Islamic religious architecture archaeological in the region of the Zab, and requirements employed in the development of religious tourism, considering that For Tourism active role in the optimal exploitation of available resources: natural, human, cultural and historical, therefore Contribute to blacken the sectorial matrix to provide jobs and create opportunities of income-generating and improve the balance of payments and the style and pattern of social and cultural life of the various members of the community. On the basis that to provide jobs and create income-generating opportunities and improve the balance of payments, as well as contribute to improving the style and pattern of social and cultural life of the various members of the community.